(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Project cannot be done without planning, scheduling and an estimation of its duration for completion. Every project that has to be undertaken must have a deadline for it completion but not every project goes as schedule. Hence, applications of scientific method such as CPM, PERT are often very useful in project management and scheduling. This study was on the application of CPM in scheduling a building construction taking a case study of Mosul Estate building construction. Analytical research design was adopted for the study as the design suit the study at hand. Secondary data of the activities, their descriptions and predecessor as while as their duration were obtained from the construction site. The network activities diagram, the forward and the backward pass obtained by the temporary ordered routing algorithm (TORA) were drawn and the critical path represented in bold arrow heads. The results show that if CPM is applied into the project, the project can be completed in 27 weeks compared to the initial duration of 32 proposed weeks by the company. This results if implemented by the management of the firm will save cost of labour and time. We recommend that CPM should be used in a building construction company before embarking on the building. The construction firm should devote more resources, labour and equipment to the critical path in order to avoid unnecessary delay and high cost of labour.